Um estudo sobre a maternidade tardia e sua relação com a individuação feminina - Carvalho, Helena Catharina Lyrio de (2015)
This study aimed at exploring the possible relationship between late motherhood and women‟s individuation process, in the light of Analytical Psychology. It is justified given the fact that the Western world has observed an increase in the proportion of women who become mothers after the age of thirty-five, period theoretically characterized by a review of one's own identity and life goals. However, even though this appears to be an issue now posed as a challenge to society, there is a dearth of research that attempt to understand the possible impact of late motherhood in the construction of woman‟s identity. A case study was conducted based on the motherhood experience of ten women who had their first child after the age of thirty-five. Through in-depth interviews we sought to capture the participants' views of their own development process. Responses were consolidated into categories, in order to identify commonalities in the developmental path of these women before and after the event of motherhood. The results showed that, when they became mothers, those women, who before had valued above all their autonomy, have apparently acquired a different and broader perspective about themselves and about others. We conclude that in such cases motherhood seems not only to have been simultaneous with a time of reviewing the meaning of life, but also to have favored an expansion of consciousness through the integration of aspects associated with acceptance of others and appreciation of the world of relationships, thus contributing to the individuation process